INFLUENCE OF HUDUMA CENTRE INNOVATION STRATEGIES ON GOVERNMENT SERVICE PERFORMANCE IN KENYA; A CASE OF KAKAMEGA COUNTY - KAGASI, VIOLET; SANGORO, MR. OSCAR; ROMAN, MR. AKETCH; OIRERE, Dr. DORCAS (IJRDO - Journal of Business Management, 2016)
In 2013, the government introduced the concept of Huduma Centres as a service delivery strategy to transform public service delivery by providing citizens access to various public services and information under one roof. The study adopted a descriptive survey design. In this study, the target population was10,595 respondents comprising of 10,560 customers, 30 operative employees and 5 managerial employees. The researcher sampled 2675 respondents by use of purposive sampling to select 5 managerial employees, stratified sampling to select 70 customers and census sampling to select 30 operative employees. The study used questionnaires, interview schedules and observation checklists as a means of collecting data which was then analysed using both descriptive and inferential statistics and presented in form of frequency, percentages and tables. This was done in sequence of objective based on hypothesis testing. The chi square and ANOVA tests were used to give the significance of the relationship between the independent and dependent variables of the objectives. It is hoped that the findings of the study may be utilised by Huduma Centre management in order to improve government service performance. The three contextual factors explained 34.5% of its variation (R2=.345, P=0.000). However, each of the factors had varied degree of effect on the government service performance with level of technology, management style and government policy in that order. The overall study recommendation is that public institution should use innovation strategies to streamline operations, capture new markets and set themselves apart in service delivery in public institutions which are known to offer substandard services to the tax payers.